Tuning the optical properties of spiro-centered charge-transfer dyes by extending the donor or acceptor part. Issue 21 (3rd October 2019) - Wössner, Jan S.; Grenz, David C.; Kratzert, Daniel; Esser, Birgit
Abstract : Spiroconjugated charge-transfer dyes with N–CO-substructure are presented, whose optical properties are tuned by extending the donor or acceptor part. Abstract : Charge-transfer-based materials with intramolecular donor–acceptor structure are widely used in technological applications. A separation of donor and acceptor through a tetrahedral spiro center leads to a rigid orthogonal arrangement. Furthermore, spiroconjugation can enhance efficient charge transfer. We herein present the syntheses, structural, electrochemical and optical properties of spiro-based CT compounds with diamine donors and diketone acceptors supported by TDDFT calculations. All compounds showed strong charge transfer in their absorbance spectra. Extending the acceptor or donor part of these compounds led to materials with emissions from the CT states. These results can aid the future design of spiro-DA-compounds towards achieving the desired optical properties.